2015
DOI: 10.1111/jnu.12167
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Its Prevention Among Intensive Care Nurses

Abstract: More measures must be taken to prevent bullying. Nurses must be educated to accept only a zero tolerance to bullying and to report bullying when confronted by bullying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 30 publications
3
51
1
Order By: Relevance
“…In this study, hospitals were the most frequently assessed healthcare setting. Nurses’ workplace‐unit specification has been also indicated in previous studies as a potential factor that may affect exposure to bullying (Fang et al, 2016; Ganz et al, 2015; Oh et al, 2016b; Spector, Zhou, & Che, 2014). Furthermore, Oh et al (2016b) and Yun et al (2014) revealed that working in more specialized units is significantly predictive of a higher risk of being bullied.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, hospitals were the most frequently assessed healthcare setting. Nurses’ workplace‐unit specification has been also indicated in previous studies as a potential factor that may affect exposure to bullying (Fang et al, 2016; Ganz et al, 2015; Oh et al, 2016b; Spector, Zhou, & Che, 2014). Furthermore, Oh et al (2016b) and Yun et al (2014) revealed that working in more specialized units is significantly predictive of a higher risk of being bullied.…”
Section: Discussionmentioning
confidence: 81%
“…In total, seven studies comprising 2,284 participants that calculated a mean score for the entire NAQ‐R scale were included: Trepanier, Fernet, and Austin (2016), Ganz et al (2015), Yun et al (2014), Laschinger et al (2010), Topa and Moriano (2013), Purpora and Blegan (2015) and Oh, Uhm, and Yoon (2016a). A total of 42.9% ( N = 3) of the studies was performed in North America, with the same number ( N = 3) in Asia; only one study (14.3%) was performed in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Other research supports the differences in reported exposure found within this study. Studies (DeKeyser et al, 2015;Lee, Bernstein, Lee, & Nokes, 2014) have shown that while uncivil behaviors existed across healthcare settings and professions, nurses were more likely to be victims. Others (Carayon & Gurses, 2008;Dellasega, 2011;Roche, Diers, Duffield, & Catling-Paull, 2010;Vessey, Demarco, Gaffney, & Budin, 2009) found that healthcare providers working in acute care arenas, or areas within high patient acuity levels, were more likely to experience incivility, stress, and burnout than their counterparts working in areas deemed less stressful.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive care nurses are exposed to various psychological risks with the potential of psychological harm, such as burnout, compassion fatigue, moral distress, and bullying . These harms have been the focus of a large body of international research exploring illbeing or the “negative side” of well‐being .…”
Section: Introductionmentioning
confidence: 99%